Time volunteered on community health activities by brigadistas in Nicaragua - Meredith Adamo; Dixmer Rivera; Rashed Shah; Jeanne Koepsell; Leonel Martínez; Justo Pastor Ortiz; Carlos José Jarquín Navarrete; David R. Marsh
ABSTRACT Objective To report on how brigadistas ("health brigadiers") in Nicaragua volunteer their time before the introduction of expanded responsibilities (beyond the scope of integrated community case management (iCCM)) for sick children 2-59 months old. Methods Three complete teams of brigadistas (n = 12 brigadistas total) were selected from remote communities in the department of Matagalpa. Each respondent brigadista was interviewed privately regarding the frequency and duration (i.e., preparation, round-trip travel, and implementation time) of 13 separate activities. The correlation between their overall estimates and summed times of individual activities were measured. Results Brigadista mean density was 1 per 156 total population (range: 120-217). Each team had one encargado/a ("manager") with an iCCM drug box plus two to four asistentes ("assistants"). All resided in the community they served. Eight reported competing time demands during one to nine months of the year. Brigadistas volunteered an average of 75 hours per month (range: 35-131). Encargados were busier than asistentes (98 versus 68 hours per month). Three activities accounted for 70% of their time: 1) iCCM (30%: treatment (11%), follow-up (19%)); 2) receiving training (21%); and 3) promoting birth planning (19%). Brigadistas' time was divided among preparation (12%), travel (27%), and implementation (61%). Overall estimates were highly correlated (+0.70) with summed implementation time. Conclusions Brigadistas from these remote Nicaraguan communities were busy with different activities, levels of effort, and patterns of task-sharing. These findings, plus an ongoing job satisfaction survey and a follow-on time study after the introduction of the new interventions, will inform policy for this valuable volunteer cadre.